Evaluasi Pelaporan Keuangan Berdasarkan PSAK No.1 Pada PT. Kereta Api Indonesia (Persero) Divisi Regional III Kota Palembang - Jesynt Destodita Zafwa; Mega Silvia (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
In an era of increasingly intense competition within the transportation industry, transparency and accountability in financial reporting have become critical aspects for ensuring the sustainability and public trust in State-Owned Enterprises. PT Kereta Api Indonesia (Persero), as a national land transportation service provider, has adopted the SAP ERP system to enhance the efficiency and accuracy of financial transaction recording. This study aims to evaluate the financial reporting practices of PT Kereta Api Indonesia (Persero) Regional Division III Palembang based on the provisions of the Indonesian Financial Accounting Standards (PSAK) No. 1 on the Presentation of Financial Statements. The research methods employed include direct observation, document analysis, and interviews with relevant personnel within the Divre III Palembang environmentBased on the findings from interviews and a review of the financial statementsit can be concluded that PT KAI Divre III Palembang has prepared its financial reports in accordance with PSAK No. 1. This is evidenced by the well-structured and appropriately classified presentation of the statement of financial position, the statement of profit or loss and other comprehensive income, and the statement of cash flows, all of which are in line with the applicable accounting standaritaion.